Impact of blanching and drying on antioxidant contents and antioxidant activity of Indian mustard leaves (Brassica juncea) (Journal of Oilseed Brassica, 2026)
Leafy vegetables contain significant amount of bio-active health promoting compounds which act as antioxidants that can impart health benefits beyond basic nutrition. Blanching and dehydration by drying are processes commonly used in preservation of leafy vegetables. The present investigation was planned to study the effect of blanching and drying on antioxidant contents (total phenols, flavonoids, Vitamin C and  carotene) and antioxidant activity of mustard leaves. In the present investigation the fresh mustard leaves were collected in a lot, washed thoroughly and divided into three portions, i.e. raw, blanched and dried to know the impact of processing (i.e. blanching and drying) on the antioxidant contents and antioxidant activity. Raw blanched and dried samples were analyzed for antioxidant contents and antioxidant activity through standard methods. Results of the study revealed that fresh mustard leaves contained total phenol 48.37 ± 0.45mg/100g GAE , flavonoids 9.17 ± 0.30 mg/100g QE, vitamin C 12.65 ± 6.01 mg/100g and  carotene 6.30±0.20 mg/100g and antioxidant activity was 46.50 ± 2.90 mg/100g AAE. The antioxidant contents and antioxidant activity of mustard leaves were found influenced by processing treatments (blanching and drying), Blanching caused loss while drying increased the concentration of antioxidant contents.